Control Centre for Intensive Care as a Tool for Effective Coordination, Real-Time Monitoring, and Strategic Planning During the COVID-19 Pandemic - Komenda, Martin; Černý, Vladimír; Šnajdárek, Petr; Karolyi, Matěj; Hejný, Miloš; Panoška, Petr; Jarkovský, Jiří; Gregor, Jakub; Bulhart, Vojtěch; Šnajdrová, Lenka; Májek, Ondřej; Vymazal, Tomáš; et al. (JMIR. Journal of medical internet research, 2022)
In the Czech Republic, the strategic data-based and organizational support for individual regions and for providers of acute care at the nationwide level is coordinated by the Ministry of Health. At the beginning of the COVID-19 pandemic, the country needed to very quickly implement a system for the monitoring, reporting, and overall management of hospital capacities. The aim of this viewpoint is to describe the purpose and basic functions of a web-based application named "Control Centre for Intensive Care," which was developed and made available to meet the needs of systematic online technical support for the management of intensive inpatient care across the Czech Republic during the first wave of the pandemic in spring 2020. Two tools of key importance are described in the context of national methodology: one module for regular online updates and overall monitoring of currently free capacities of intensive care in real time, and a second module for online entering and overall record-keeping of requirements on medications for COVID-19 patients. A total of 134 intensive care providers and 927 users from hospitals across all 14 regions of the Czech Republic were registered in the central Control Centre for Intensive Care database as of March 31, 2021. This web-based application enabled continuous monitoring and decision-making during the mass surge of critical care from autumn 2020 to spring 2021. The Control Center for Intensive Care has become an indispensable part of a set of online tools that are employed on a regular basis for crisis management at the time of the COVID-19 pandemic.
Keywords: pandemie; Humans; strategické plánování; lidé; péče o pacienty v kritickém stavu; SARS-CoV-2; Strategic Planning; Pandemics; COVID-19; Critical Care